Oral presentations difficulties and its causes: preliminary analysis of UiTM Kelantan students / Anis Idayu Aziz, Wan Nazihah Wan Mohamed and Nor Hairunnisa Mohammad Nor - Aziz, Anis Idayu; Wan Mohamed, Wan Nazihah; Mohammad Nor, Nor Hairunnisa (Universiti Teknologi MARA Cawangan Pulau Pinang, 2022)
The ability to perform oral presentations is one of the skills that students need to acquire throughout their learning years. Doing English presentations is always challenging among students, particularly Malay students who use English as their second language. Previous studies highlighted that second language learner usually struggle to complete oral presentation tasks. This study aims to identify the difficulties faced when making oral presentations and the causes of difficulties encountered by 155 students at UiTM Kelantan Branch. A questionnaire consisting of the items on the difficulties faced during the oral presentation and their reasons was adapted from previous studies. The questionnaire was distributed to research participants who enrolled in courses that included oral presentation as the main form of assessment. Descriptive analysis was employed to fulfil the objectives of the study. Based on the results, the main difficulties faced by students during their oral presentations were forgetting what to say, making grammatical errors, and not being confident talking in public. In relation to this, the students faced these difficulties due to a lack of confidence and not having good voice qualities, such as being clear and loud enough to be heard when delivering a speech. The analysis of this study would enable the students to identify the problems faced during oral presentations, which could assist them in overcoming the issues, thus, preparing them well in oral presentation skills during the tertiary level of education before embarking into the workforce environment. On the part of instructors, they could set up adequate practice activities for students to have enough confidence before the actual presentation. Further studies are suggested to investigate the impact of practice in improving students' oral presentations.